Endothelin‐1 modulates methacholine‐induced cutaneous vasodilatation but not sweating in young human skin. (11th March 2016) - Halili, Lyra; Singh, Maya Sarah; Fujii, Naoto; Alexander, Lacy M.; Kenny, Glen P.
Abstract : Key points: Endothelin‐1 (ET‐1) is a potent endothelial‐derived vasoconstrictor that may modulate cholinergic cutaneous vascular regulation. Endothelin receptors are also expressed on the human eccrine sweat gland, although it remains unclear whether ET‐1 modulates cholinergic sweating. We investigated whether ET‐1 attenuates cholinergic cutaneous vasodilatation and sweating through a nitric oxide synthase (NOS)‐dependent mechanism. Our findings show that ET‐1 attenuates methacholine‐induced cutaneous vasodilatation through a NOS‐independent mechanism. We also demonstrate that ET‐1 attenuates cutaneous vasodilatation in response to sodium nitroprusside, suggesting that ET‐1 diminishes the dilatation capacity of vascular smooth muscle cells. We show that ET‐1 does not modulate methacholine‐induced sweating at any of the administered concentrations. Our findings advance our knowledge pertaining to the peripheral control underpinning the regulation of cutaneous blood flow and sweating and infer that ET‐1 may attenuate the heat loss responses of cutaneous blood flow, but not sweating. Abstract: The present study investigated the effect of endothelin‐1 (ET‐1) on cholinergic mechanisms of end‐organs (i.e. skin blood vessels and sweat glands) for heat dissipation. We evaluated the hypothesis that ET‐1 attenuates cholinergic cutaneous vasodilatation and sweating through a nitric oxide synthase (NOS)‐dependent mechanism. Cutaneous vascular conductance (CVC) and sweat rate were assessed in three protocols: in Protocol 1 ( n  = 8), microdialysis sites were perfused with lactated Ringer solution (Control), 40 pm, 4 nm or 400 nm ET‐1; in Protocol 2 ( n  = 11) sites were perfused with lactated Ringer solution (Control), 400 nm ET‐1, 10 mm N G ‐nitro‐l ‐arginine (l ‐NNA; a NOS inhibitor) or a combination of 400 nm ET‐1 and 10 mm l ‐NNA; in Protocol 3 ( n  = 8), only two sites (Control and 400 nm ET‐1) were utilized to assess the influence of ET‐1 on the dilatation capacity of vascular smooth muscle cells (sodium nitroprusside; SNP). Methacholine (MCh) was co‐administered in a dose‐dependent manner (0.0125, 0.25, 5, 100, 2000 mm, each for 25 min) at all skin sites. ET‐1 at 400 nm ( P  < 0.05) compared to lower doses (40 pm and 4 nm ) (all P  > 0.05) significantly attenuated increases in CVC in response to 0.25 and 5 mm MCh. A high dose of ET‐1 (400 nm ) co‐infused withl ‐NNA further attenuated CVC during 0.25, 5 and 100 mm MCh administration relative to the ET‐1 site (all P  < 0.05). Cutaneous vasodilatation in response to SNP was significantly blunted after administration of 400 nm ET‐1 ( P  < 0.05). We show that ET‐1 attenuates cutaneous vasodilatation through a NOS‐independent mechanism, possibly through a vascular smooth muscle cell‐dependent mechanism, and methacholine‐induced sweating is not altered by ET‐1. Key points: Endothelin‐1 (ET‐1) is a potent endothelial‐derived vasoconstrictor that may modulate cholinergic cutaneous vascular regulation. Endothelin receptors are also expressed on the human eccrine sweat gland, although it remains unclear whether ET‐1 modulates cholinergic sweating. We investigated whether ET‐1 attenuates cholinergic cutaneous vasodilatation and sweating through a nitric oxide synthase (NOS)‐dependent mechanism. Our findings show that ET‐1 attenuates methacholine‐induced cutaneous vasodilatation through a NOS‐independent mechanism. We also demonstrate that ET‐1 attenuates cutaneous vasodilatation in response to sodium nitroprusside, suggesting that ET‐1 diminishes the dilatation capacity of vascular smooth muscle cells. We show that ET‐1 does not modulate methacholine‐induced sweating at any of the administered concentrations. Our findings advance our knowledge pertaining to the peripheral control underpinning the regulation of cutaneous blood flow and sweating and infer that ET‐1 may attenuate the heat loss responses of cutaneous blood flow, but not sweating.